Korean species of the genus Amischa Thomson (Coleoptera: Staphylinidae: Aleocharinae), with a description of new species - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2023)
A taxonomic study of the genus Amischa Thomson of Korea is presented. The genus is represented in Korea by three species, including A. koreana Lee & Ahn, sp. nov. Amischa analis (Gravenhorst) is reported for the first time in the Korean peninsula. A key to Korean species, descriptions, habitus photographs, and illustrations of the diagnostic characters are provided.